Enhancing Healthcare Data Security and Integrity through Blockchain Technology in Hospital Information Systems - Hu Ming; Shamsul Arrieya Bin Ariffin (Malikussaleh University, Aceh, Indonesia, 2025)
The goal of this research is to develop and test a blockchain-based framework whose target is to increase the level of security of, integrity , and operational efficiency in hospital information systems (HIS). As the increasing number of sensitive healthcare data and the increasing threats to data privacy, the following system integrates AES encryption, multi-factor authentication (MFA), role-based access control (RBAC), blockchain storage and smart contracts to ensure secure and transparent data management. The methodology was that the framework was implemented in a simulated environment using the Hyperledger Fabric v2.2 on Ubuntu 20.04, and performance was measured for various metrics such as encryption time, transaction time, storage efficiency, scalability, and system responsiveness. Comparative analysis was done to evaluate the user related metrics like ease of use, adoption rate and user satisfaction against the benchmarked metrics reported in the previous body of literature. The results indicate that the blockchain-based system is better than the traditional cloud-based and distributed systems, offering 80% of speeds of transactions, 90% storage efficacy, 85% of scaling, 95% of security, 90% of ease of use, and 80% of adoption. These results show the potentiality of blockchain in improving reliability, auditability, and trustworthiness of information systems in healthcare.